IMPACT OF CONVERTING AGRICULTURAL LAND INTO AN OIL AND GAS MINING AREA IN GAYAM DISTRICT, BOJONEGORO REGENCY - Tria Mei Hidayati; Hamidah Hendrarini; Dona Wahyuning Laily (RADJA PUBLIKA, 2024)
Bojonegoro Regency has the nickname